2013
DOI: 10.1111/j.1348-0421.12035
|View full text |Cite
|
Sign up to set email alerts
|

Pyriproxyfen enhances the Immunoglobulin G immune response in mice

Abstract: Pyriproxyfen is a juvenile hormone mimic of vital importance for insect development with little risk to humans. This study was performed to investigate whether large doses of pyriproxyfen affect the immune response in mammals. Mice were immunized thrice with ovalbumin in 5% ethanol, with or without pyriproxyfen or alum. Large doses of pyriproxyfen (9 or 15 mM) significantly enhanced specific total IgG immune response. This enhancement was no longer present 24 hr after treatment with pyriproxyfen. These results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Several studies suggest that insect hormones play a role in mammalian physiology in part by functioning as a modulator of nuclear receptors since these hormones and analogs have similarities with ligands of mammalian nuclear receptors (No et al ; Kizelsztein et al ; Sharmin et al ). Recently, we reported that PYR, a synthetic JH analog, enhances TR4 transcriptional activity, which promotes lipid accumulation in 3 T3‐L1 adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest that insect hormones play a role in mammalian physiology in part by functioning as a modulator of nuclear receptors since these hormones and analogs have similarities with ligands of mammalian nuclear receptors (No et al ; Kizelsztein et al ; Sharmin et al ). Recently, we reported that PYR, a synthetic JH analog, enhances TR4 transcriptional activity, which promotes lipid accumulation in 3 T3‐L1 adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has shown that insect hormones affect various aspects of mammalian physiology. Because of structural or/and functional similarities of ecdysteroids and JHs with mammalian hormones such as steroids, derivatives of vitamins A and D3 and isoprenoids, several studies have suggested that these hormones may function as physiological modulators in mammals in part through transactivation of mammalian nuclear receptors Kizelsztein et al 2009;Sharmin et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies showed that chronic exposure to pesticides has a close relationship with a higher risk of various cancers (Alavanja et al 2004). The effect of PYR on mammalian physiology has been reported in several studies (Matsunaga et al 1995;Yoshino et al 1995Yoshino et al , 1996Sharmin et al 2013). Matsunaga et al (1995) reported that PYR and its derivatives are rapidly excreted and only trace amount of their residues are detected in blood, kidney and liver.…”
Section: Introductionmentioning
confidence: 99%
“…; Sharmin et al . ). Because of the profound structural and/or functional similarities of these hormones between insects and mammals, many studies have demonstrated physiological effects of 20E and JH in mammals.…”
Section: Introductionmentioning
confidence: 97%
“…In mammals, lipophilic hormones, such as steroids, derivatives of vitamins A and D3 and isoprenoids, play important roles in reproduction, development and metabolism. These molecules act by binding to cognate receptors, which regulate transcription of a variety of genes (Wurtz et al 2000;Kizelsztein et al 2009;Sharmin et al 2013). Because of the profound structural and/or functional similarities of these hormones between insects and mammals, many studies have demonstrated physiological effects of 20E and JH in mammals.…”
Section: Introductionmentioning
confidence: 99%